Analisis Efisiensi Penggunaan Teknologi Aspal Daur Ulang Pada Jalan Tol Elevated Ir. Wiyoto Wiyono - Yogi Oktopianto; Dwi Wahyu Hidayat (Borneo Engineering : Jurnal Teknik Sipil, 2020)
The use of recycling technologies to the principles of green roads should get priority. Reclaimed Asphalt Pavement (RAP) has not been used properly is a problem in this study. Hotmix Recycling is a recycling technique that can be applied to road pavement rehabilitation and maintenance. The research was conducted to determine the cost-efficiency of recycled asphalt. The method used in this research is to analyze the unit price of conventional asphalt maintenance and to analyze the unit price of recycled asphalt in order to find out how much efficiency is obtained of asphalt pavement recycled. The results showed that the cost of conventional asphalt is Rp.1,160,000 per ton and the price of recycled asphalt is Rp.915,000 per ton, there is a savings of Rp. 245,000 per ton, The use of recycled asphalt technology in the periodic asphalt of the Ir. Wiyoto Wiyono toll roads can save operational and maintenance costs of Rp. 3,013,500,000.00